Ontological Framework for analyzing Student’s Emotional behavior performance enhancement using Fuzzy Logic - kumar, Kirthika Ashok (International Journal of Psychosocial Rehabilitation, 2020)
Personality refers to variations in one’s personal attributes subjected to various events throughout the accustomed life cycle in an individual. The projection of the individual’s mind in a behavioral activity also depicts one’s personality. In the paper a framework for analyzing a University Student’s performance efficiency for a job at workplace has been proposed. Students have been classified psychologically for determining overall efficiency based on different aspects such as emotional level, holistic approach, confidence level, stress and time management. The psychological factors and the relationships between them is depicted as an Emotion Ontology which gives a clear understanding for the system to be developed in the future based on the framework. By improving the individual traits efficiency of a person can have ameliorations which get reflected in the person’s work environment. The data set for training the proposed system is to be collected through questionnaires from which linguistic values are fed as input to the fuzzy Inference Engine along with association rules. The output of the system would also be a linguistic value with which the efficiency of the person is determined.